Kapital Sosial dalam Mendukung Pendidikan Anak pada Keluarga Rentan - Sunan, Moch. Ilham Noer; Azzahra, Cut Afra; Lawang, Robert MZ; Nugrahini, Triyanti (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
Grounded in Coleman’s view of social capital as trust, norms, and reciprocal relationships that support purposeful action, and Bourdieu’s framework in which habitus, various forms of capital, and the field interact to shape educational practices, this study examines how these dynamics influence the learning experiences of children from three vulnerable families in a rural community. Using a qualitative case study approach, data were collected through semi-structured interviews, field notes, and documentation, and then analyzed thematically to explore how family relationships, daily routines, and digital access shape children’s learning processes. The findings show that each family carries a distinct configuration of social and digital capital that produces different habitus and leads to varied educational practices. The first family demonstrates strong social capital, warm relationships, and functional use of digital technology, enabling the child to overcome limitations in the learning environment. The second family reflects weak social capital, an unstable habitus, and digital engagement dominated by entertainment, resulting in inconsistent study habits and low learning motivation. The third family exhibits a supportive habitus, positive peer networks, and purposeful digital engagement, allowing the child to develop independent learning strategies despite a limited parental educational background. Overall, the study reveals that children’s educational outcomes in vulnerable families are shaped not merely by economic constraints but by the interplay between relational quality, internal dispositions, social networks, and digital competence within the field of schooling. These findings underscore the importance of strengthening family communication, fostering meaningful digital literacy, and building supportive social networks to sustain children’s learning in resource-limited environments.